Degradation of 3-chloropropionic acid by escherichia coli JM109 expressing dehalogenase (deh) gene used as selection marker - Tan, Yea Yusn (Asian Network for Scientific Information, 2009)
3-Chloropropionic acid (3CP) in its carboxylate ionic form is a synthetic compound found in herbicide. The biodegradability of 3CP is not well documented but a microbe that has the ability to utilise 3CP as sole carbon and energy source has been isolated. The dehalogenase gene (deh) cloned from Rhodococcus sp. HJ1 could be used as a selection marker gene for vector in E. coli. Halogenated compound, especially 3CP inhibit the growth of some microorganisms. In current investigation, a 4 kb EcoR1 fragment of genomic DNA from Rhodococcus sp. HJ1 was cloned into pUC18 plasmid and transformed into an E. coli JM109 conferred 3CP resistance on them. Therefore, E. coli transformed with vector marked with deh could be easily selected on plates containing 3CP. The E. coli JM109 transformed with pTY096 (deh+) weakly expressed the deh gene as shown from its slow growth with cells doubling time of 22 h with minimal amount of chloride ion released in the growth medium